Touching Earth: Drawing as Intra-action and Entanglement in Here, Down Below - Kosma, Anthi (BBDS - Black Book: Drawing and Sketching, 2025)
The following article presents experiences, observations, and graphic material from the Imprográfika experimental workshop, titled “Here, Down Below”, a drawing workshop dedicated to earth. Specifically, we focus on one of the workshop’s units, “Clay Notebooks”, where we explored whether and how soil can transform from a descriptive subject into the very material of drawing, and how matter and traces can intertwine in more complex intra-actions and entanglements. By investigating drawing as a means of fostering a deeper connection to nature, emphasis is placed on drawing as exploration, touch, medium, and agent that operates beyond visual-, anthropo-, and logo-centric regimes. The aim is not only to reconnect, understand, interpret, or protect the fragile earth but also to shift paradigms and move toward drawing as a symbiotic, spontaneous, and ecological gesture. This approach seeks to redefine drawing’s materiality and reveal mark-making as a multifaceted practice of inscriptions, imprints, and interfaces. As a starting point and primary reference, we drew on the work of visual artist Miquel Barceló, focusing on his performance-based mud drawings created in collaboration with choreographer Josef Nadj and captured in the documentary Clay Diaries (2011). This multifaceted tracing performance, centered on the fluidity of mud’s materiality, served as reference that introduced drawing as an ongoing becoming—far removed from drawing as an object, a finished representation, or other dualistic approaches. Earthly traces, transcriptions, and textures can touch and be touched, opening up the imaginary of drawing beyond the human and the natural as separate entities, toward the phantasmatic of surviving times, multiple stratifications, and sensitivities.